Menganalisis Identitas Visual dari Diptyque Paris - Casimira, Clarissa (Jurnal Vicidi, 2024)
This journal explores the impact of visual identity design on consumer perception and brand recognition, using the luxury brand Diptyque as a case study. The study analyzes how Diptyque’s synchronized design elements—such as logos, typography, color palettes, and illustrations—communicate the brand’s personality and influence customer loyalty. The research aims to provide insights for Micro, Small, and Medium Enterprises (MSMEs) on building effective visual identities by analyzing Diptyque’s successful branding strategies. The qualitative research method involved expert interviews and literature reviews. Experts in branding and design were interviewed to assess the effectiveness of Diptyque’s visual identity in conveying brand values. The study found that Diptyque’s distinctive oval-shaped logo, minimalist black-and-white palette, and hand-drawn illustrations play a significant role in establishing the brand’s luxury status and emotional appeal. Consistency in applying these design elements reinforces brand recognition and loyalty. The findings suggest that a well-defined and cohesive visual identity is crucial for brands to stand out in a competitive market. Diptyque’s example offers valuable lessons for MSMEs on how to use design elements strategically to enhance customer perceptions and build lasting brand presence.